Reducing the grid orientation dependence of flow routing on square-grid digital elevation models - Hyväluoma, Jari (Taylor & Francis, 2017)
Topographical parameters derived from digital elevation models by employing flow routing algorithms may depend on the orientation of the square grid. Grid orientation dependence results from the insufficient isotropy of square grid and affects the flow directions and subsequent calculations based on flow routing. In this article, a systematic approach for analysing the rotational invariance of flow accumulation calculations is presented and applied. Computed flow accumulation maps are found to depend strongly on the grid orientation, especially if flow routing methods with low dispersion are used. It is also shown that isotropy of flow routing algorithms can be significantly improved by introducing a numerical parameter resulting in adjustable weighting for cardinal and diagonal directions in flow routing. The actual value of this parameter depends on the used flow routing method.
Keywords: flow distribution; digital elevation model; rotational invariance; isotropy; grid orientation